Overwintering success in adults of the Japanese common grass yellow Eurema mandarina. Issue 2 (15th January 2018) - Konagaya, Tatsuro; Yokoi, Tomoyuki; Watanabe, Mamoru; Numata, Hideharu
Abstract: The evolution of reproductive diapause is controversial in males as compared to females that must overwinter to leave offspring, because late‐autumn males can obtain offspring by pre‐overwintering copulation. The Japanese common grass yellow Eurema mandarina is suitable to examine the evolution of male reproductive diapause, because direct comparisons are possible between males that do and do not exhibit reproductive diapause. Approximately one‐half of males are insensitive to diapause‐inducing conditions, and emerge as non‐diapause summer‐form. Most autumn‐form females mate with summer‐form males in late autumn. Females that have overwintered re‐mate with autumn‐form males before the onset of oviposition. Because last‐male‐precedence is general in sperm competition in Lepidoptera, it is unclear why half of males emerge as summer‐form in late autumn. A potential adaptive benefit for emerging as summer‐form is increased sperm overwintering success, if autumn‐form females have a higher overwintering success than autumn‐form males. In the present study, overwintering success was estimated for both sexes of autumn‐form adults by rearing under seminatural conditions and a mark–release–recapture technique. Both approaches estimated an overwintering success of approximately 5% for both sexes. The absence of difference in overwintering success between the sexes suggests that pre‐overwintering copulation does not increase sperm overwintering success. However, a considerably low overwintering success may explain, at least partly, the presence of summer‐form males in late autumn. The degree of overwintering success might be more important than the sexual differences of overwintering success in the evolution of male reproductive diapause. Abstract : We found that both sexes of autumn‐form adults in the Japanese common grass yellow Eurema mandarina suffered a considerably low overwintering success (approximately 5%) both in an experiment under seminatural conditions and in the mark–release–recapture experiment. This low overwintering success may relate to the evolution of males without reproductive diapause in late autumn.